2018
DOI: 10.3390/su11010137
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Water Seed Drill

Abstract: Water content plays a crucial role in seed development, particularly at the seed sowing stage, and it ensures good seed germination. A water seed drill was designed and developed to provide an optimum quantity of water that is required for the soil in the same furrow, right after seed placement. This soil moistening method not only improves the moisture level in the field, but it also saves a large amount of water by applying the needed water quantity in the line of sowing after seed placement. The water seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…One of the causes of land degradation is erosion. This is in accordance with [13] which states that critical land from an erosion perspective is defined as agricultural land with conditions where the rate of soil loss due to rainwater exceeds the rate of soil formation itself. The erosion that occurs will transport soil to the top layer of soil, namely fertile soil that is rich in nutrients, so the greater the erosion that occurs, the more soil fertility will decrease.…”
Section: Chemical Propertiessupporting
confidence: 83%
“…One of the causes of land degradation is erosion. This is in accordance with [13] which states that critical land from an erosion perspective is defined as agricultural land with conditions where the rate of soil loss due to rainwater exceeds the rate of soil formation itself. The erosion that occurs will transport soil to the top layer of soil, namely fertile soil that is rich in nutrients, so the greater the erosion that occurs, the more soil fertility will decrease.…”
Section: Chemical Propertiessupporting
confidence: 83%
“…However, this corresponds to the inquiry of (Kumara et al, 2021). On another terrain, the stride of (Noor et al, 2019) indicated higher yields with the usage of the seed drill. It is further implored that agribusiness farmers should leverage other platforms to enhance the comprehensive ease of operating the seed drill.…”
Section: Statementmentioning
confidence: 88%
“…After 30-35 days, the grafted plants under uniform growing (temperature and humidity) conditions were transplanted into greenhouse having 20 m x 50 m (1000 m 2 ) dimensions. The land was prepared conventionally for all treatments using M.B plough, Disc harrow, cultivator and soil leveler (Noor et al, 2019a). The soil characteristics were pH 7.3, electrical conductivity (EC) 0.14 mS cm −1 , NO3 15 mg dm 3 , P 4 mg•dm 3 , K 31 mg dm 3 , Ca 28 mg dm 3 , Mg 17 mg dm 3 , and total nitrogen 0.25%.…”
Section: Methodsmentioning
confidence: 99%